Development of an Integral Management System (GIS) to improve project management in sanitation works in local governments. - Hidalgo Aguilar, Omar Julinho (2020)
The document that is presented addresses the problem of frequent deviations that occur in the management of projects, poor execution of work in time. Cost and specifications, which finally marks the planned utilities for the projects, as well as the consequent dissatisfaction of the clients that as a client usually does not perform a control task but rather leaves all the activities to the supervisor and this entails no Take action before the events occur. All this is basically linked to the ¡nadequate supervision and execution of work in the construction processes by the companies, that is, do not count or apply a method, system to carry the work properly. The main objective of this work is to develop an integrated system of Process Management for the client (public entity), all from the compatibility of the technical file completed and approved to then move on to the elaboration of the TDRs supervision and Construction from where the necessary requirements are placed that the client requires to be able to manage the project planning and controlling the necessary actions to get a good control of the project requesting to the supervisor and contractor basic information that allow to take preventive and corrective actions in such a way that Can have a positive impact in the course of the Project.